2022
DOI: 10.47836/pjtas.45.3.18
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Plant Growth Regulators to Enhance Arsenic Phytostabilization by Pennisetum purpureum cv. Mott

Abstract: The limited translocation of arsenic from contaminated soil to plant biomass is one way to decrease human exposure to arsenic (As). Plant growth regulators (PGR), including salicylic acid, indole butyric acid, and calcium, have been reported to alleviate toxicity and decrease the accumulation of heavy metals in many plants. Thus, this study has investigated the effect of plant growth regulators, including salicylic acid, salicylic acid + calcium chloride, indole butyric acid, and indole butyric acid + calcium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…purpureum cv. Mott, also known as elephant grass or Napier grass, is a versatile forage crop with remarkable characteristics (Chouychai & Somtrakoon, 2022). It is well-suited for cultivation in marginal lands due to its adaptability to various environmental conditions (Putra et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…purpureum cv. Mott, also known as elephant grass or Napier grass, is a versatile forage crop with remarkable characteristics (Chouychai & Somtrakoon, 2022). It is well-suited for cultivation in marginal lands due to its adaptability to various environmental conditions (Putra et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Pennisetum purpureum cv. Mott has found utility in phytoremediation, specifically in soils contaminated with substances such as Arsenic (As) (Chouychai and Somtrakoon, 2022;Kowitwiwat and Sampanpanish, 2020) and heavy metals (Putra et al, 2022), However, it exhibits limitations in adapting to saline soil conditions (Pongtongkam et al, 2006) and faces challenges related to biomass production and root growth in acidic soils (Putra et al, 2022;Kowitwiwat and Sampanpanish, 2020) reported reduced chlorophyll content in Pennisetum purpureum cv. Mott when grown in tailing soil contaminated with heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…Napier grass was reported to be an effective choice for phytoremediation. Dwarf Napier grass has been reported to phytostabilize arsenic in soil (Chouychai & Somtrakoon, 2022;Kowitwiwat & Sampanpanish, 2020). This grass species is also reportedly used in the phytoremediation of petroleum hydrocarboncontaminated soil (Ologidi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%